Effect of constitutive expression of Arabidopsis CLAVATA3 on cell growth and possible role of cytokinins in leaf size control in transgenic tobacco plants - Kuluev, Bulat (Journal of plant physiology, 2018)
Copyright © 2018. Published by Elsevier GmbH.